PENGARUH KEPUASAN DAN LOYALITAS PELANGGAN TERHADAP WORD OF MOUTH PADA PELANGGAN HONDA MOTOR DI SURABAYA - Yuli Rahmawati; Bagus Suminar (Journal of Business & Banking, 2014)
This study aims to determine whether increased sales and increased production that occurs at the Honda motor company were due to customers satisfaction, loyalty, and word of mouth. The method of analysis was done by means of multiple linear regression analysis andpath analysis. The data were collected through a survey questionnaire. Questionnaires were distributed to Honda customers who were inadvertently encountered. They were the customers of Honda motorcycles with more than one year. The measurement was done by Likert with a scale of one to five. It shows there is a significant influence of customer satisfaction towards customer loyalty, and also found a significant influence of customer loyalty towards word of mouth, as well as a significant influence of customer satisfaction toward word of mouth, and found also the influence indirect customer satisfaction on word of mouth throughcustomer loyalty. It is important to strengthen the company's relationships with customers. In this case customer satisfaction is also an important aspect. Satisfaction and loyalty can be a key objective in improving and maintaining word of mouth, while customer word of mouth will come up when customer satisfaction and customer loyalty have been created.